A Multi‐responsive Fluorescent Probe Reveals Mitochondrial Nucleoprotein Dynamics with Reactive Oxygen Species Regulation through Super‐resolution Imaging. (13th July 2020) - Yang, Guanqing; Liu, Zhengjie; Zhang, Ruilong; Tian, Xiaohe; Chen, Juan; Han, Guangmei; Liu, Bianhua; Han, Xinya; Fu, Yao; Hu, Zhangjun; Zhang, Zhongping
Abstract: Understanding the biomolecular interactions in a specific organelle has been a long‐standing challenge because it requires super‐resolution imaging to resolve the spatial locations and dynamic interactions of multiple biomacromolecules. Two key difficulties are the scarcity of suitable probes for super‐resolution nanoscopy and the complications that arise from the use of multiple probes. Herein, we report a quinolinium derivative probe that is selectively enriched in mitochondria and switches on in three different fluorescence modes in response to hydrogen peroxide (H2 O2 ), proteins, and nucleic acids, enabling the visualization of mitochondrial nucleoprotein dynamics. STED nanoscopy reveals that the proteins localize at mitochondrial cristae and largely fuse with nucleic acids to form nucleoproteins, whereas increasing H2 O2 level leads to disassociation of nucleic acid–protein complexes. Abstract : Triple threat : A mitochondria‐targeting probe switches on in three different fluorescence modes in response to H2 O2, protein, and nucleic acids, enabling the visualization of mitochondrial nucleoprotein dynamics. Super‐resolution imaging reveals that the proteins localize at mitochondrial cristae and largely fuse with nucleic acids to form nucleoproteins, whereas increasing H2 O2 levels lead to disassociation of the nucleoproteins.